Please don't lie : a thriller - Kline, Christina Baker, 1964-; Burt, Anne (Thomas & Mercer, 2025)
"Two years ago, Hayley Stone lost everything. First, her parents died in a devastating fire. Then, her sister overdosed, leaving Hayley alone and hounded by a media circus that turned her family's tragedy into tabloid fodder. When her new husband suggests a fresh startin the Adirondacks, the promise of anonymity in an isolated mountain town feels like salvation. But the mountains hold darker secrets than she ever imagined. Her once-loving husband grows distant and volatile. The widow down the road keeps spewing vague accusations. Not even their new friends--a free-spirited couple living on the property--can help Hayley shake the creeping sense that something is off. As winter edges closer, Hayley discovers that her sanctuary is anything but safe. Trapped and isolated, she faces a terrifying truth: in trying to escape her past, she may have run straight into something far more dangerous."--Provided by publisher.